2002
DOI: 10.1002/jsfa.1057
|View full text |Cite
|
Sign up to set email alerts
|

Thermal gelation of brown trout myofibrils from white and red muscles: effect of pH and ionic strength

Abstract: The effects of pH and ionic strength on the thermal gelation of brown trout myo®brils from white and red muscles were analysed by thermal scanning rheometry. The highest gelation ability was obtained at low pH (around 5.6) whatever the ionic strength. No effect of ionic strength was observed at pH 5.6; however, at pH 6.0, lowering the salt (KCl) concentration to 0.3 M or less improved the characteristics of the gels formed. The effects of pH and ionic strength on myo®brils from both muscle types appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
6
14
1
Order By: Relevance
“…6. The scallop actomyosin gel showed the highest strength at pH 5.6 (12.83 g), which was consistent with previously reported results for myofibrils extracted from brown trout [3]. The high gel strength of scallop actomyosin at pH 5.6 was primarily due to the aggregation of protein molecules.…”
Section: Gel Strengthsupporting
confidence: 93%
See 1 more Smart Citation
“…6. The scallop actomyosin gel showed the highest strength at pH 5.6 (12.83 g), which was consistent with previously reported results for myofibrils extracted from brown trout [3]. The high gel strength of scallop actomyosin at pH 5.6 was primarily due to the aggregation of protein molecules.…”
Section: Gel Strengthsupporting
confidence: 93%
“…pH is considered to be one of the most important factors affecting the gelation ability of myofibrillar protein. Proteins from fish are more sensitive to changes in pH than those from mammals and can only form a gel in a narrow pH range [3]. The optimum pH for gelation ability is often reported to be between 5.5 and 7.0 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that mild protein oxidation can improve the protein gel network by changing the arrangement of myosin, while excessive oxidation can produce a large number of aggregates that cannot form a dense gel network structure [55][56][57]. Lund et al [58] showed…”
Section: Gel Strengthmentioning
confidence: 99%
“…Numerous studies have shown that mild protein oxidation can improve the protein gel network by changing the arrangement of myosin, while excessive oxidation can produce a large number of aggregates that cannot form a dense gel network structure [55][56][57]. Lund et al [58] showed that the oxidation of thiol groups of proteins transformed into intermolecular disulfide bonds and affected the stiffness and elasticity of protein gels. The addition of CE promotes protein unfolding, as confirmed by the exposure of hydrophobic groups in previous studies [25], which may disrupt the hydrogen bonding of α-helix and promote the conversion of α-helix to other three secondary structures.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…[4] It is a complex dynamic process that the secondary structure and the structural features of the myofibrillar proteins changed significantly in the process of heating. [5] Heat-induced gelation properties based on interactions among myofibrillar proteins are dependent on many factors, such as pH, ionic strength, protein concentration, type of muscle as well as the heat-induced temperature and so forth, [6,7] especially pH and ionic strength. [1,8,9] The previous studies had mainly focused on water-holding capacity, texture, and the qualitative microstructure; [10][11][12][13][14][15] however, quantitative ultrastructural studies are rarely executed in details.…”
Section: Introductionmentioning
confidence: 99%